2017
DOI: 10.1044/2017_jslhr-s-16-0206
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Communicative Participation in Amyotrophic Lateral Sclerosis

Abstract: Purpose People with amyotrophic lateral sclerosis frequently experience bulbar impairment and dysarthria that may restrict their ability to take part in everyday communication situations. The aim of this study is to examine selected variables that may contribute to restrictions in communicative participation. Method Community-dwelling participants with amyotrophic lateral sclerosis ( N = 70) who reported commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 11 publications
1
13
0
3
Order By: Relevance
“…Similarly, other studies examining communicative participation in other patients (including those with head and neck cancer, multiple sclerosis, and amyotrophic lateral sclerosis) using a longer, 46-item version of the CPIB reported levels of communicative participation that were also comparable with the facial paralysis sample represented in this study. [20][21][22] A comparison of communicative participation between these samples is shown in the Figure. 19 -22 Although we are cautious in making direct comparisons between these different patient groups (as they may have differing perspectives and expectations regarding their communicative function), it is surprising to see that the sample in this study subjectively reported levels of communicative participation that are comparable with those in patients with known, severe communicative disorders, such as those who have undergone laryngectomy. These findings are consistent with prior qualitative research that reported that patients with various disorders that affect verbal communication (spasmodic dysphonia, multiple sclerosis, Parkinson disease, and amyotrophic lateral sclerosis) experienced similar types of restrictions in communicative participation despite different mechanisms of speech impairment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, other studies examining communicative participation in other patients (including those with head and neck cancer, multiple sclerosis, and amyotrophic lateral sclerosis) using a longer, 46-item version of the CPIB reported levels of communicative participation that were also comparable with the facial paralysis sample represented in this study. [20][21][22] A comparison of communicative participation between these samples is shown in the Figure. 19 -22 Although we are cautious in making direct comparisons between these different patient groups (as they may have differing perspectives and expectations regarding their communicative function), it is surprising to see that the sample in this study subjectively reported levels of communicative participation that are comparable with those in patients with known, severe communicative disorders, such as those who have undergone laryngectomy. These findings are consistent with prior qualitative research that reported that patients with various disorders that affect verbal communication (spasmodic dysphonia, multiple sclerosis, Parkinson disease, and amyotrophic lateral sclerosis) experienced similar types of restrictions in communicative participation despite different mechanisms of speech impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Samples from the literature included laryngectomy, 19 head and neck cancer (HNCa), 20 amyotrophic lateral sclerosis (ALS), 21 and multiple sclerosis (MS). 22 facial paralysis on daily living and highlight the importance of incorporating patient-reported outcome measures in the management of fac ial paralysis.…”
Section: Facial Paralysismentioning
confidence: 99%
“…To provide perspective on the relative degree of communicative dysfunction experienced by patients with facial paralysis compared to those suffering from other conditions, the mean CPIB logit score for patients in this study was compared to previously published means for different patient populations: patient who previously underwent a laryngectomy; were treated for laryngeal, oropharyngeal, oral, or multi-primary head and neck cancer; or with a diagnosis of amyotrophic lateral sclerosis (ALS) or multiple sclerosis (MS). 15-19 Figure 1 displays the CPIB logit mean and standard deviation from this study (left) and from multiple previously published studies. The logit allows for comparisons across studies and ranges from −3 to +3 with lower scores indicating worse communicative function.…”
Section: Resultsmentioning
confidence: 98%
“…The predictive relationship between monologue intelligibility and communicative participation illustrates the pronounced impact of dysarthria on engagement in life activities. It is well documented that the communication changes associated with hypokinetic dysarthria cause individuals with PD to demonstrate a significant decrease in their self-perceived communication skills [14,27,28], but the specific relationship between intelligibility and communicative participation has not been sufficiently studied [30,31,52].…”
Section: Discussionmentioning
confidence: 99%